IN ALL THE RELATION OF EARLY AMBULATION WITH PERINEUM INJURY RECOVERY AT POST PARTUM MOTHER WORK AREAS OF SINGOSARI LOCAL CLINIC OF MALANG REGENCY - SLI, Dina Dewi; Ratnawati, Retty; Berlian, Intan (Jurnal Keperawatan, 2012)
Early ambulation is policy to guide the patients out of their bed and guide to walk as son as possible. Early ambulation able to avoid blood flow obstruction. The blood flow obstruction able to cause interior thrombosis vena and able to cause infection. Early ambulation is external factor beside injury treatment. While the internal factor is eat pattern or consumption pattern. Also influence the recovery sped of perineum injury. The research aimed at knowing the early mobilization 2-4 hours and 6-8 hours with recovery speed of perineum injury of post partum mother in the work areas of Singosari local clinic of Malang Regency. The research method was comparative design with cohort approach. Samples were selected by purposive sampling of 16 respondents of post partum mother with perineum injury of grade 2 and independent variable that were measured was early ambulation and dependent variable was recovery speed of perineum injury. Data analysis by fisher. The results showed that significant value of 1,000 that higher than alfa = 0,05. From data analysis it can be concluded that it means no differences between early mobilization 2-4 hours with 6-8 hours.